2018
DOI: 10.4236/ojog.2018.813142
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Outcome of Cases of Placenta Previa with and without Morbidly Adherent Placenta at King Abdul-Aziz University Hospital, Saudi Arabia

Abstract: Introduction: Worldwide increasing cesarean section rates are expected to have a parallel increase in the number of cases of Placenta Previa with all the expected complications, including pathologically adherent placenta. This morbidly adherent placenta constitutes a serious and possibly a life threatening complication. An efficient team capable for managing possible complicated situations will be able to reduce mortality and morbidity. Objectives: The aim of our study was to evaluate maternal outcome in cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…Generally, the incidence of PP among other Saudi studies ranged from 0.41-1.6%. [18][19][20][21][22][23] In a previous report from AMCH, Saudi Arabia, by Bahar et al 21 the total incidence of PP was 0.73% which is comparable to our study )0.69%(. An earlier study from AMCH by Zaki et al 23 reported an incidence of PP patients delivered by C-sections )meaning major degree( to be 0.48%, which is marginally less than our study )0.55%(.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Generally, the incidence of PP among other Saudi studies ranged from 0.41-1.6%. [18][19][20][21][22][23] In a previous report from AMCH, Saudi Arabia, by Bahar et al 21 the total incidence of PP was 0.73% which is comparable to our study )0.69%(. An earlier study from AMCH by Zaki et al 23 reported an incidence of PP patients delivered by C-sections )meaning major degree( to be 0.48%, which is marginally less than our study )0.55%(.…”
Section: Resultssupporting
confidence: 90%
“…The percentage of patients with PP and a previous cesarean delivery is up to 75-96% among PP/PAS patients. [18][19][20][21][22][23] In AMCH, over the last 2 decades )2000-2021(, the percentage of PP patients with one previous C-section had increased from approximately 57% )in a previous study by Bahar et al 21 ( to ~61% in the current study. It is recommended that every pregnant woman with a previous cesarean delivery should have a placental localization during a mid-pregnancy routine fetal anomaly scan.…”
Section: Resultsmentioning
confidence: 42%
See 2 more Smart Citations
“…PPP leads to insufficient blood supply to the placenta, inducing placental adhesion or implantation, making it difficult for the placenta to be separated from the mother during delivery. It increases the risk of postpartum bleeding and endangering the life of the mother and child (Chitkara et al., 2020 ; Radwan et al., 2018 ; Ryu et al., 2019 ; Shah et al., 2020 ). According to the report, the incidence of placenta previa with placental implantation was 25% and 40% in women with a history of first and second caesarean sections, respectively.…”
Section: Introductionmentioning
confidence: 99%